Identification of a Novel Serum Biomarker for Tuberculosis Infection in Chinese HIV Patients by iTRAQ-Based Quantitative Proteomics - Chen, Cong; Yan, Tao; Liu, Liguo; Wang, Jianmin; Jin, Qi (Frontiers in Microbiology, 2018)
Tuberculosis (TB) is a major comorbidity in HIV patients as well as a serious co-epidemic. Traditional detection methods are not effective or sensitive for the detection of Mycobacterium tuberculosis at the early stage. TB has become a major cause of lethal on HIV patients. In the study, we employed isobaric tags for relative and absolute quantitation (iTRAQ) technology to identify the different host responses in HIV-noTB and HIV-TB patients’ sera. Given the diversity of HIV subtypes, which results in a variety of host responses in different human populations, we focused on Chinese patients. Of the 25 proteins identified, 7 were increased and 18 were decreased in HIV-TB co-infected patients. These proteins were found to be involved in similar immune response processes. Importantly, we identified a candidate protein, Endoglin (ENG), which showed a 4.9 times increase by iTRAQ method and 11.5 times increase by ELISA. ENG demonstrated the diagnostic efficacy and presented a novel molecular biomarker for TB in HIV-infected Chinese patients. This study provides new insight into the challenges in the diagnosis and effective management of patients with HIV-TB.